Rethinking Romanization: roman expansion in Italy as seen through ancient historical accounts - Scopacasa, Rafael (Revista de História, 2015)
Between the fourth and second centuries BC, Rome conquered practically all of peninsular Italy, and founded numerous colonies in lands that were confiscated from Italian communities. Roman historical writers provide detailed accounts of the wars and battles fought during this period, but say little about the political, legal and socio-economic arrangements made between Rome and Italian communities after the wars. This article discusses some of the social interactions that developed as a result of the Roman expansion in Italy between the fourth and second centuries BC, by identifying key historical agents that participated in this process and how they interacted. I argue that knowledge of these social interactions can provide a deeper understanding of how Roman hegemony impacted on the daily lives of conquered peoples. Ultimately, this discussion can contribute towards a new framework for understanding the effects of Roman hegemony in the Mediterranean world.